Multifaceted Aid for Low-Income Students and College Outcomes: Evidence from North Carolina - Charles T. Clotfelter; Steven W. Hemelt; Helen F. Ladd (Institute for the Study of Labor (IZA), 2016)
Launched in 2004, the Carolina Covenant combines grant-heavy financial aid with an array of non-financial supports for low-income students at an elite public university. We find that the program increased four-year graduation rates by about 8 percentage points for eligible students in the cohorts who experienced the fully developed program. For these cohorts, we also find suggestive effects on persistence to the fourth year of college, cumulative earned credits, and academic performance. We conclude that aid programs targeting low-income, high-ability students are most successful when they couple grant aid with strong non-financial supports.
Keywords: I21; I22; I23; I24; 330; postsecondary completion; financial aid